Analog PBX system designed for MIMOS / Abdul Ghafar Ali and Fauziah Fadzil - Ali, Abdul Ghafar; Fadzil, Fauziah (1992)
The purpose of this project is to design Subscriber Line Interface Circuit (SUC) and Dual Tone Multi-frequency (DTMF) cards for a low capacity analog PBX system. The basic hardware model of analog PBX system consists of five parts. They are Backplane or Interconnection Board with Ringing Generator, SLIC card, Switching network, DTMF Transceiver, Tone Generator and Control processor. As the receiver Is off-hook, the scanner unit notifies the control processor which connects the telephone to a tone generator and a dial tone is heard. When the user begins dialing, the tone generator is disconnected and DTMF Receiver responsible for recognizing the dialed digit is connected. The digits are stored until a complete set Is recognized, and the control processor interprets them. A path is built through the switch to specified destination port, where a ring signal Is applied. When the scanner notifies the control processor that the received party has gone off-hook, the calling port is connected to the called port through the switch and the call set-up is completed.